2016
DOI: 10.1590/0104-1428.1926
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de propriedades dinâmico-mecânicas de um compósito aeronáutico de CFRP com fios de ligas com memória de forma embebidos

Abstract: Resumo Este trabalho trata-se de um estudo experimental do comportamento de propriedades termomecânicas de um compósito ativo, obtido através da introdução de diferentes frações volumétricas de fios de uma liga NiTi com efeito de memoria de forma em uma matriz polimérica reforçada com fibras de carbono (CFRP). Para tal estudo, inicialmente fez-se uma análise do módulo elástico de um pré preg de CFRP aeronáutico com diferentes posições de ângulo de fibras de carbono, a fim de determinar a matriz mais adequada p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Villar et al [64] reported the difficulty of the adhesion between the SMA metal alloys and the polymeric matrix. The sample studied consisted in a sandwich composite of resin and fibers, the reinforcement of SMA threads.…”
Section: Polymeric Composites Reinforced With Shape Memory Alloysmentioning
confidence: 99%
“…Villar et al [64] reported the difficulty of the adhesion between the SMA metal alloys and the polymeric matrix. The sample studied consisted in a sandwich composite of resin and fibers, the reinforcement of SMA threads.…”
Section: Polymeric Composites Reinforced With Shape Memory Alloysmentioning
confidence: 99%
“…Villar et al [21] noticed the difficulty of adhesion between the SMA metallic alloys and polymeric matrix. The studied sample consisted of a sandwich composite, resin and fiber layers, reinforced with SMA wires.…”
Section: Introductionmentioning
confidence: 99%
“…Vilar et al [17], in your research, studied the dynamic-mechanical properties of a composite reinforced with carbon-fiber with NiTi wires. This work attributed the reduction of elasticity modulus to the softening of matrix, and the fraction of the NiTi in the composition of the sample.…”
Section: Introductionmentioning
confidence: 99%